Reconstructing applicable chaotic Baptista-type symmetric cryptosystem - Daud, Muhamad Azlan (2014)
This work, introduces a method to repair a cryptosystem based on a chaotic dynamical system. Baptista exploited the chaotic property of the logistic equation f(x) = b x (1 - x) to develop a cryptosystem. This cryptosystem has the ability to produce various ciphers responding to the same message input. Alvarez through his one-time pad attack successfully attacked the Baptista cyptosystem. Ariffin attempted to modify the cryptosystem to enhance the security of the original Baptista’s cryptosystem. Rhouma identified a flaw in the method Ariffin put forward, specifically in step 4 of the encryption procedure, where it does not implement a oneto- one operation resulting in failure to decrypt the ciphertext. The method is based on the Fractal and Iterated System (IFS), where an in-depth study on Fractal, Chaos and Cryptography is needed to assist in actualizing the research objectives. The algorithm is developed to counter the one-time pad attack. This recommended encryption algorithm also overcomes the flaw in Ariffin’s encryption procedure. The modified Baptista type cryptosystem suffers from message expansion that goes against the conventional methodology of a symmetric cryptosystem. As a result, we studied the idea of Huffman encoding. We then designed a new compression algorithm developed using ideas from the Huffman coding. Finally, the compression algorithm is applied onto the modified Baptista cryptosystem to show a possible practical deployment of the Baptista cryptosystem and to also produce better compression ratio.